Thinking head: Towards human centred robotics - Herath, D C; Kroos, C; Stevens, C J; Cavedon, L; Premaratne, P (2010 11th International Conference on Control Automation Robotics and Vision, 2010)
Thinking Head project is a multidisciplinary approach to building intelligent agents for human machine interaction. The Thinking Head Framework evolved out of the Thinking Head Project and it facilitates loose coupling between various components and forms the central nerve system in a multimodal perception-action system. The paper presents the overall architecture, components and the attention system. The paper then concludes with a preliminary behavioral experiment that studies the intelligibility of the audiovisual speech output produced by the Embodied Conversational Agent (ECA) that is part of the system. These results provide the baseline for future evaluations of the system as the project progresses through multiple evaluate and refine cycles.